Carbon-related Materials in Recognition of Nobel Lectures by Prof. Akira Suzuki in ICCE - Kaneko, Satoru; Mele, Paolo; Endo, Tamio; Tsuchiya, Tetsuo; Tanaka, Katsuhisa; Yoshimura, Masahiro; Hui, David (Springer International Publishing : Imprint: Springer, 2017)
Details recent scientific advances in the field of carbon materials and carbon nanomaterials including: polymers, carbon nanocomposites, and graphene; Covers a wide spectrum of topics related to carbon science, from organic chemistry to devices, physical chemistry, applied physics, synthesis, and device implementation; Describes experimental and theoretical approaches in several categories of carbon-related materials. This book summarizes the recent advances in carbon-related materials. It covers both experimental and theoretical approaches in graphene and nanocarbon materials, carbon composites and thin films, organic synthesis and physical chemistry, and characterization tools. Also discussed are cutting-edge applications for use in biochemical assays, dental implant surface modifi cations, pressure sensors, and more. This book is published in recognition of the Nobel Lectures delivered by Akira Suzuki, Emeritus Professor of Hokkaido University and Nobel Prize winner in Chemistry, 2010.
Keywords: Materials science.; Polymers.; Nanochemistry.; Nanotechnology.; Ceramics.; Glass.; Composites (Materials).; Composite materials.; elektronické knihy; electronic books